1980
DOI: 10.1901/jaba.1980.13-143
|View full text |Cite
|
Sign up to set email alerts
|

The Applicability of a Helicopter Patrol Procedure to Diverse Areas: A Cost‐benefit Evaluation

Abstract: The residential burglary deterrent effects of a helicopter patrol procedure were investigated in four separate areas with a multiple baseline technology. The helicopter was flown during an 8:00 a.m. to 4:00 p.m. period in two high density population areas of approximately 9.82 and 14.71 square miles and two low density population areas of 117.49 and 89.97 square miles. The helicopter patrol reduced residential burglaries without crime displacement in the two high density areas but had no deterrent effects in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Again, we find no significant overall effect. While this is the first study on helicopters to prevent vehicle arsons, prior studies on preventing burglaries have found an effect (Schnelle et al, 1978 ; Kirchner et al, 1980 ). The coefficients are however negative, and for one city it was close to significance with about 1 less burning car than expected on days with a helicopter patrol.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Again, we find no significant overall effect. While this is the first study on helicopters to prevent vehicle arsons, prior studies on preventing burglaries have found an effect (Schnelle et al, 1978 ; Kirchner et al, 1980 ). The coefficients are however negative, and for one city it was close to significance with about 1 less burning car than expected on days with a helicopter patrol.…”
Section: Discussionmentioning
confidence: 81%
“…But the limitation is that this was a high crime area and the reduction in burglaries would be smaller in a low crime area and thereby reverse the cost benefit analysis that speaks for helicopter patrols in high crime areas (Schnelle et al, 1978). These results were replicated in a later study, but only for areas with high burglary levels and with a high population density and not in similar areas with low population density (Kirchner et al, 1980).…”
Section: Helicoptersmentioning
confidence: 88%
See 2 more Smart Citations
“…A subsequent study showed decreases in residential burglaries in high-density areas but not low-density areas when police patrols were in effect. The authors discussed a variety of issues related to effectiveness of the program and distribution of costs (Kirchner et al, 1980). A related crime reduction study found that alarms installed in cash drawers activated by the removal of bait money produced an increase in apprehensions but did not reduce robbery incidents (Schnelle et al, 1979).…”
Section: Crime and Delinquencymentioning
confidence: 99%